Associationistic luce rule - LI, Jiangtao (Institutional Knowledge at Singapore Management University, 2016)
We develop an extension of Luce’s random choice model that incorporates a role forthe association of alternatives. Each alternative is characterized by a salience value, aLuce value, and its associated alternatives. The salience value captures the alternative’sability to attract the decision maker’s attention, and the Luce value measures thealternative’s desirability. The decision maker is first attracted by some alternativeaccording to a salience-based Luce-type formula, and then chooses among its associatedalternatives according to another desirability-based Luce-type formula. While retainingthe simplicity of the Luce rule, the theory accommodates some well-known behavioralphenomena in individual choice, such as the attraction effect (violations of regularity),and violations of stochastic transitivity.